2019
DOI: 10.1162/jocn_a_01452
|View full text |Cite
|
Sign up to set email alerts
|

Tool Use Modulates Somatosensory Cortical Processing in Humans

Abstract: Tool use leads to plastic changes in sensorimotor body representations underlying tactile perception. The neural correlates of this tool-induced plasticity in humans have not been adequately characterized. This study used ERPs to investigate the stage of sensory processing modulated by tool use. Somatosensory evoked potentials, elicited by median nerve stimulation, were recorded before and after two forms of object interaction: tool use and hand use. Compared with baseline, tool use—but not use of the hand alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
(115 reference statements)
0
15
0
Order By: Relevance
“…We recently found evidence that mechanisms in somatosensory cortex for localizing touch on an arm are re-used to localize touch on a tool (Miller et al, 2019a). Furthermore, tool use leads to lasting changes in somatosensory perception (Canzoneri et al, 2013;Cardinali et al, 2011;Miller et al, 2014Miller et al, , 2017 that are likely driven by plasticity in somatosensory cortex (Miller et al, 2019b;Schaefer et al, 2004). Given the high-degree of flexibility in the somatosensory system, we propose that the computation of trilateration is also used to localize touch on tools.…”
Section: Model Predictionsmentioning
confidence: 96%
See 1 more Smart Citation
“…We recently found evidence that mechanisms in somatosensory cortex for localizing touch on an arm are re-used to localize touch on a tool (Miller et al, 2019a). Furthermore, tool use leads to lasting changes in somatosensory perception (Canzoneri et al, 2013;Cardinali et al, 2011;Miller et al, 2014Miller et al, , 2017 that are likely driven by plasticity in somatosensory cortex (Miller et al, 2019b;Schaefer et al, 2004). Given the high-degree of flexibility in the somatosensory system, we propose that the computation of trilateration is also used to localize touch on tools.…”
Section: Model Predictionsmentioning
confidence: 96%
“…We have recently demonstrated that humans can accurately localize where a tool has been touched (75) and that mechanisms in somatosensory cortex for localizing touch on an arm may be re-used to localize touch on a tool (25). Furthermore, tool use leads to lasting changes in somatosensory perception (53,76) that are likely driven by plasticity in somatosensory cortex (77). Thus, given the high-degree of flexibility in the somatosensory system, we predict that the computation of trilateration is also used to localize touch on tools.…”
Section: Is Multilateration a General Spatial Computation?mentioning
confidence: 99%
“…Since then, proprioception has been considered among the main inputs feeding this implicit body representation 37 40 . In previous work, we reported that proprioceptive deafferentation may still allow fairly accurate touch localization on a tool 41 , but prevents tool-use from affecting the subsequent kinematics 14 . This inability to incorporate a tool at motor level, at odds with what typically shown by young and now old healthy participants, attests to the crucial role of proprioceptive inputs in building an updated representation of the motor effector.…”
Section: Discussionmentioning
confidence: 96%
“…On the other side, these parents were not fully compliant with the rehabilitation during follow-ups, which could be another factor that hampered the best outcome possible. Theoretically speaking, the somatosensory cortical plasticity comes into effect after reconstruction, [23,24] constant stimuli, rehabilitation, and parental guidance would be of paramount importance. Nevertheless, when asked whether they would recommend this treatment to other fellow parents, these parents gave the score of 6 (out of 10), suggesting the likelihood of doing so.…”
Section: Discussionmentioning
confidence: 99%